London Dispersion Interactions in Pnictogen Cations [ECl2]+ and [E=E]2+ (E=P, As, Sb) Supported by Anionic N‐Heterocyclic Carbenes. Issue 71 (11th December 2018) - Ho, Luong Phong; Nasr, Alexandre; Jones, Peter G.; Altun, Ahmet; Neese, Frank; Bistoni, Giovanni; Tamm, Matthias
Abstract: Several pnictogen dihalide complexes of the type (WCA‐IDipp)EX2 (E=P, As, Sb; X=Cl, Br) that bear an anionic N ‐heterocyclic carbene ligand with a weakly coordinating borate moiety (WCA‐IDipp, WCA=B(C6 F5 )3, IDipp=1, 3‐bis(2, 6‐diisopropylphenyl)imidazolin‐2‐ylidene) were prepared by salt metathesis reactions between the respective pnictogen trihalides EX3 and the lithium salt (WCA‐IDipp)Li⋅ toluene. Two‐electron reduction of the dihalides (WCA‐IDipp)EX2 with 1, 3‐bis(trimethylsilyl)‐1, 4‐dihydropyrazine or elemental magnesium afforded the dipnictenes (WCA‐IDipp)2 E2, which display typical element‐element double bonds as observed in diaryldiphosphenes, ‐arsenes and ‐stibenes. To provide an insight into the factors contributing to the structural stability of the pnictogen dihalide and dipnictene compounds, quantum chemical calculations were performed at the domain‐based local pair natural orbital coupled‐cluster (DLPNO‐CCSD(T)) level. A local energy decomposition (LED) analysis of the interaction between the carbene and the pnictogen dihalide or dipnictene moiety demonstrates that London dispersion is an essential factor for the stabilization of these compounds. Abstract : London calling : Several pnictogen complexes of the type (WCA‐IDipp)EX2 and (WCA‐IDipp)2 E2 (E=P, As, Sb; X=Cl, Br) that bear anionic N ‐heterocyclic carbene ligands with a weakly coordinating borate moiety were prepared. To provide an insight into the factors contributing to the structural stability, quantum chemical calculations were performed involving for instance Local Energy Decomposition (LED) analysis.